2018
DOI: 10.1002/er.3968
|View full text |Cite
|
Sign up to set email alerts
|

A direct carbon solid oxide fuel cell fueled with char from wheat straw

Abstract: Summary Direct carbon solid oxide fuel cell (DC‐SOFC) is a promising technology for electricity generation from biomass with high conversion efficiency and low pollution. Biochar derived from wheat straw is utilized as the fuel of a DC‐SOFC, with cermet of silver and gadolinium‐doped ceria as the material of both cathode and anode and yttrium stabilized zirconia as electrolyte. The output performance of a DC‐SOFC operated on pure wheat straw is 197 mW cm−2 at 800°C and increases to 258 mW cm−2 when 5% of Ca, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Apparently, the single cell gives a high initial voltage of 0.65 V and a relatively stable discharging platform from beginning to end. The discharging time lasts for 21 h, corresponding to a released electric quantity of 7560 C. Considering the overall reaction as a four‐electron reaction (C + 2O 2− = CO 2 + 4e), the pepper straw char consumed in the system is 0.24 g. Accordingly, the fuel utilization of the microtubular DC‐SOFC is 44.4% calculated from Faraday's law with 0.54 g char as feedstock, which is obviously higher than that with other biomass fuels . The result has once again proven that the pepper straw containing natural catalysts is an ideal fuel for the DC‐SOFCs.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Apparently, the single cell gives a high initial voltage of 0.65 V and a relatively stable discharging platform from beginning to end. The discharging time lasts for 21 h, corresponding to a released electric quantity of 7560 C. Considering the overall reaction as a four‐electron reaction (C + 2O 2− = CO 2 + 4e), the pepper straw char consumed in the system is 0.24 g. Accordingly, the fuel utilization of the microtubular DC‐SOFC is 44.4% calculated from Faraday's law with 0.54 g char as feedstock, which is obviously higher than that with other biomass fuels . The result has once again proven that the pepper straw containing natural catalysts is an ideal fuel for the DC‐SOFCs.…”
Section: Resultsmentioning
confidence: 92%
“…Currently, many types of biomass derived from crop residues, such as corn cob char, leaf char, wheat straw, bagasse, pomelo peel char, and walnut shells, have been adopted as carbon fuels to improve the cell performance due to the naturally existing catalysts of the reverse Boudouard reaction. Cai et al developed an electrolyte‐supported solid oxide fuel cell (SOFC), which yielded a maximum power density of 197 mW cm −2 at 800 °C using wheat straw as fuel. An et al found that pomelo peel char is a promising solid carbon fuel for DC‐SOFCs, and the single cell achieved a maximum power density of 309 mW cm −2 at 850 °C with the fuel utilization of 47.25%.…”
Section: Introductionmentioning
confidence: 99%
“…Fuel cells (FCs) are electrochemical devices that are used for direct conversion of chemical energy of fuels into electricity with high efficiency. Besides high efficiency, fuel cells have several advantages such as silent, smaller in size compared to other energy conversion devices, low or no environmental impact [6], moreover, it can work on different fuels that can be obtained from renewable resources such as methanol [7], ethanol [8], formic acid [9], biogas [10,11], syngas [12], and biochar [13]. Moreover, FCs are also used for simultaneous wastewater treatment and electricity generation, such as in urea fuel cells [14] and microbial fuel cells [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Solid oxide fuel cell (SOFC) is an all‐solid‐state power generating equipment that can directly convert chemical energy in fuel into electricity via electrochemical reactions . Because of its high efficiency and fuel flexibility (hydrogen, methane, carbon, and even wheat straw), SOFC shows a good application prospect and attracts much research attention. In laboratory studies of SOFC, performance testing is commonly conducted upon button cells because of easy implementation and low cost .…”
Section: Introductionmentioning
confidence: 99%
“…Solid oxide fuel cell (SOFC) is an all-solid-state power generating equipment that can directly convert chemical energy in fuel into electricity via electrochemical reactions. 1 Because of its high efficiency and fuel flexibility (hydrogen, 1 methane, 2 carbon, 3,4 and even wheat straw 5 ), SOFC shows a good application prospect and attracts much research attention. In laboratory studies of SOFC, performance testing is commonly conducted NOMENCLATURE: d, diameter of the inner gas tube, cm; j, current density, A/m 2 ; j 0 , exchange current density, A/m 2 ; j ref , reference exchange current density, A/m; j TPB , electric current generated in unit TPB length, A/m; p ref , partial pressure at reference conditions, pa; p TPB , partial pressure at TPBs, pa; p, pressure of gas species, pa; u, velocity of gas flow, m/s; x, molar fraction; D, diameter of button cell, cm; E eq , equilibrium electrical potential difference, V; F, Faraday constant, 96 485 C/mol; H, vertical distance between anode surface and inlet of gas channel, cm; N, molar flux of gas species, mol/(m 2 s); R, gas constant, 8.314 J/(mol K); T, operating temperature, K; U, output voltage, V; V FR , flow rate of fuel gas Greek letters: ρ, density, kg/m 3 ; ϕ, electrical potential, V; μ, dynamic viscosity, Pa·s; κ, permeability, m 2 ; ε p , porosity of electrode; λ TPB , TPB length in unit volume (m/m 3 ); σ eff , effective conductivity, S/m; σ 0 , material intrinsic conductivity, S/m; Ψ, volume fraction; η local , local overpotential, V Subscripts: el, electronic conducting phase; io, ionic conducting phase; inlet, inlet of gas channel; local, local reaction sites; ref, reference conditions; TPB, triple-phase boundaries; H 2 , hydrogen; O 2 , oxygen Superscripts: a, anode side; c, cathode side upon button cells because of easy implementation and low cost.…”
Section: Introductionmentioning
confidence: 99%